Simulation of photovoltaic airflow windows for indoor thermal and visual comfort and electricity generation - Haredy, Abdullah (2016)
The alleviation of heating (in winter), cooling (in summer), artificial lighting and electricity use in office facilities is defined as a bioclimatic trend that offers sustainable building practice through a semi-transparent building integrated photovoltaic thermal envelope as a photovoltaic airflow window system. This thesis aims to produce synthesised design and strategies for the use of a proposed airflow window unit in office building in any given location and to maximise use of the renewable energy. Computational Fluid Dynamics (CFD), namely ANSYS Fluent 14.0, and ECOTECT have been employed to model the mechanical and natural ventilation of an office building integrated with a semi-transparent photovoltaic airflow window and the daylighting impact of various PV transparent degrees (15, 20, 25, 30 and 35 per cent) on the interior space, respectively, for winter and summer conditions. The use of such software has urged to establish a validation analysis a priori in order to ascertain the applicability of the tools to the targeted examination. The validation process involved a comparison of the results of CFD turbulence models, first, against benchmark and, second, against results of literature for identical component. The results of ECOTECT, in terms of daylight factor and illuminance level, were also compared against the results of Daysim/radiance, Troplux and BC/LC found in the literature. Excellent agreement was attained from the comparison of the results with errors less than 10 per cent. The study presents results of modelling of the airflow window system integrated into an office room for energy efficiency and adequate level of thermal and visual comfort. Results have revealed that the combination of mechanical and buoyancy induced flow spreads the heat internally warming the space to be thermally acceptable during the heating season whilst the mechanical convection is a main force for the cooling season. The thermal and visual comfort was compared for different PV airflow window transparent levels to determine the optimum PV transparency for the office space. Moreover, time-dependant and steady state conditions were imposed to predict the thermal and air behaviour for more elaborate investigation. The transient analysis was carried out, in sequential and individual base, according to the solar irradiance of each minute of working period, 8am-4pm (winter) and 5am-7pm (summer). The results obtained from transient and steady state, for both seasons, were compared and revealed negligible impact of transient effect. The PV electricity output was calculated from each transparency level under each condition, summer and winter (transient and steady). The predicted flow patterns, temperature distribution and the daylight factors in the room have been used to determine the most appropriate opening locations, sizes and system specifications for maintaining a comfortable indoor environment. The simulation investigation show that, for the proposed window model, optimum thermal and visual performance can be achieved from the PV transparency level of 20 per cent, during the heating season, and from the PV transmittance of 15 per cent, during the cooling season, where the PV output is highest. However the PV transparencies of 25, 30 and 35% can be reliable under altered conditions of operation.